2015
DOI: 10.3109/17435390.2015.1030792
|View full text |Cite
|
Sign up to set email alerts
|

Cerium dioxide nanoparticles affectin vitrofertilization in mice

Abstract: Due to their catalytic and oxidative properties, cerium dioxide nanoparticles (CeO2NPs) are widely used as diesel additive or as promising therapy in cancerology; yet, scarce data are available on their toxicity, and none on their reproductive toxicity. We showed a significant decrease of fertilization rate, assessed on 1272 oocytes, during in vitro fertilization (IVF) carried out in culture medium containing CeO2NP at very low concentration (0.01 mg.l(-1)). We also showed significant DNA damage induced in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 34 publications
2
49
0
Order By: Relevance
“…Moreover, it has been shown that CeO 2 NPs induce oxidative stress and genotoxicity in human skin melanoma cells and human dermal fibroblasts [59, 60]. A more recent study has shown that low and more relevant concentration of CeO 2 NPs (0.01 mg/L) adversely affected in vitro fertilization in mice and caused DNA damage in mouse spermatozoa and oocytes [61]. The observed DNA damage was explained by the direct impact of CeO 2 NPs and/or mechanical impact on the disruption of gamete interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been shown that CeO 2 NPs induce oxidative stress and genotoxicity in human skin melanoma cells and human dermal fibroblasts [59, 60]. A more recent study has shown that low and more relevant concentration of CeO 2 NPs (0.01 mg/L) adversely affected in vitro fertilization in mice and caused DNA damage in mouse spermatozoa and oocytes [61]. The observed DNA damage was explained by the direct impact of CeO 2 NPs and/or mechanical impact on the disruption of gamete interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the same research group has demonstrated earlier the accumulation of CeO 2 NPs along oocyte zona pellucida [62]. Finally, it has also been suggested that CeO 2 NPs could negatively impact fertilization by causing oxidative stress [61]. …”
Section: Discussionmentioning
confidence: 99%
“…During in vitro fertilization of mouse 1272 oocytes, we showed a significant decrease of fertilization rate, at a very low concentration (0.01 mg L −1 ) of CeO 2 NPs. We also showed significant DNA damage induced in vitro by CeO 2 NPs on mouse spermatozoa and oocytes at the same low concentration [37][38][39] using the Comet assay. As an orthogonal method, we used transmission electron microscopy to determine the location of accumulation of the particles within or outside the cells.…”
Section: Iiic Ceo 2 and Reprotoxicity (Pra 3)mentioning
confidence: 67%
“…It was recently shown that serum proteins form a corona and can modulate genotoxicity of NMs . Hence, not only ROS production but also direct binding to/physical disruption of membranes or proteins such as tubulins and/or actins , altered protein conformation, RNA binding , mechanical stress leading to changes in downstream cellular signalling pathways may be at work to induce genotoxicity, therefore suggesting new MoA.…”
Section: Changing Paradigms For Nms’ Genotoxicitymentioning
confidence: 99%